Nocturnal Glucose Control with an Artificial Pancreas at a Diabetes Camp - Phillip, Moshe; Battelino, Tadej; Atlas, Eran; Kordonouri, Olga; Bratina, Natasa; Miller, Shahar; Biester, Torben; Avbelj Stefanija, Magdalena; Muller, Ido; Nimri, Revital; Danne, Thomas (The New England journal of medicine, 2013)
This randomized, crossover trial compared an artificial-pancreas system with a sensor-augmented pump for nocturnal glucose control in young persons with type 1 diabetes at a diabetes camp. The artificial pancreas resulted in less hypoglycemia and tighter glucose control. Intensive insulin therapy is considered to be the standard treatment for tight blood glucose control in patients with type 1 diabetes, since it prevents long-term complications. Several studies have promoted the use of insulin pumps, glucose sensors, or a combination of the two devices (sensor-augmented pump) 1 – 3 to improve glucose control. However, the risk of hypoglycemia is still present with the use of all currently available therapies. 4 – 6 Maintenance of nocturnal euglycemia is extremely important and is challenging, since most cases of severe hypoglycemia occur at night. 7 , 8 Such episodes account for 75% of total hypoglycemic seizures in children 9 and . . .